2013
DOI: 10.4103/2141-9248.113659
|View full text |Cite
|
Sign up to set email alerts
|

Do women presenting for first and second-trimester abortion differ socio-demographically?

Abstract: Background:To identify the socio-demographic differences between a sample of women who present for first-trimester and second-trimester abortion.Aim:To determine whether women presenting late (in the second trimester) for abortion differ socio-demographically from those presenting early (in the first trimester).Materials and Methods:Data over 4 years for women presenting for second-trimester abortion were collected from the records of Family Planning Clinic at a public tertiary level teaching hospital in India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(14 reference statements)
0
8
1
Order By: Relevance
“…This study demonstrated that the overall prevalence of induced second trimester abortion was 19.2% which is in line with the prior study in South Africa that was 20% [ 26 ]. However, the finding of this study is greater than the global reported proportion 10–15% [ 10 ], study done in Nigeria 10% [ 8 ] and New Delhi 2% [ 27 ]. The possible explanation might be due to many women presenting to the government hospitals because private health institutions are not equipped to provide abortion care beyond 12 weeks of gestation except in rare occasions like private hospitals staffed by specialists (obstetrician/gynecologist).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This study demonstrated that the overall prevalence of induced second trimester abortion was 19.2% which is in line with the prior study in South Africa that was 20% [ 26 ]. However, the finding of this study is greater than the global reported proportion 10–15% [ 10 ], study done in Nigeria 10% [ 8 ] and New Delhi 2% [ 27 ]. The possible explanation might be due to many women presenting to the government hospitals because private health institutions are not equipped to provide abortion care beyond 12 weeks of gestation except in rare occasions like private hospitals staffed by specialists (obstetrician/gynecologist).…”
Section: Discussioncontrasting
confidence: 73%
“…A study done in New Delhi showed that factors affecting having second trimester abortion are difficulty in recognition of pregnancy and delay related to logistic problems [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Economic and logistical constraints, lack of information about providers, [ 7 , 8 , 10 , 11 , 21 ], and geographical characteristics [ 8 , 10 ] have been identified as key barriers to seeking first trimester and presenting for second trimester abortion in the US and Colombia. We also identified distance (residing outside Mexico City) as a barrier.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to a study carried out in Delhi where it was observed that second trimester abortions are directly proportional to an increase in parity. 13 This difference could have risen due to the small sample size (n=84) investigated by the researchers compared to ours (n=202). The number of second trimester abortions seen by the researchers was 2% of the total while our findings showed second trimester abortions constituting 25% of the total.…”
Section: Discussionmentioning
confidence: 69%